Attitudes to sexting amongst post-primary pupils in Northern Ireland: a liberal feminist approach. Issue 8 (17th November 2021) - York, Leanne; MacKenzie, Alison; Purdy, Noel
ABSTRACT: This study focuses on sexting amongst young people in Northern Ireland about which there is, as yet, very little qualitative research. To address the gap, and using a liberal philosophical feminist framework, focus group interviews were conducted with seventeen (ten girls and seven boys) 16–17-year-olds to explore their views on sexting. The young people in this study regard sexting as normal behaviour and report that it is more likely to be boys who pressure girls for a picture, a common finding in sexting research. Unlike the literature, however, this study found that girls also instigate sexting and put pressure on boys to send pictures. Despite this finding, there is still an unequal relationship between girls and boys largely because of the objectification of girls (and, rarely, boys).